A pilot study of the effect of curcumin on epigenetic changes and DNA damage among patients with non-alcoholic fatty liver disease: A randomized, double-blind, placebo-controlled, clinical trial. (June 2020) - Hariri, Mitra; Gholami, Ali; Mirhafez, Seyed Reza; Bidkhori, Mohammad; Sahebkar, Amirhosein
Highlights: Using phytosamal form of curcumin in patients with non-alcoholic fatty liver. Studying the effect of phytosomal curcumin on epigenetic changes in patients with non-alcoholic fatty liver. Studying the effect of phytosomal curcumin on DNA damage in patients with non-alcoholic fatty liver. Phytosomal curcumin can change promoter methylation of MLH1 and MSH2 in patients with non-alcoholic fatty liver. Abstract: Background: The enhancement of oxidative stress in non-alcoholic fatty liver disease (NAFLD) patients may cause mutation in DNA by deamination of cytosine to 5-hydroxyuracil or uracil. This study aimed to discover the effects of curcumin on NAFLD progress, DNA damage caused by oxidative stress, and promoter methylation of mismatch repair enzymes. Material and methods: in this study, 54 NAFLD patients were randomly devided into two groups, according to a double blind parallel design either phytosomal curcumin (250 mg/day) or placebo for 8 weeks. Fasting blood samples and anthropometric measures were taken twice, once at the baseline and once at the end of the study. Promoter methylation and 8-hydroxy-2′ -deoxyguanosine (8−OHdG) concentration as DNA damage mediator were measured by restriction enzymes and enzyme-linked immunosorbent assay, respectively. Result: Analysis was performed on 44 patients. According to our between groups analysis, curcumin significantly reduced the methylation in MutL homolog 1 (MLH1) and MutS homolog 2 (MSH2) promoter regions. The within-group comparison revealed that anthropometric variables significantly decreased. However, the result of the between groups comparison indicated no significant changes in the anthropometric variables except for BMI. Liver enzymes and 8−OHdG did not significantly change at the end of the study, neither in curcumin group nor in placebo group. Conclusion: Curcumin might be able to reduce the risk of mismatch base pair in DNA among the NAFLD patients. However, it did not change the DNA damage mediator and liver enzymes. For confirming these results, more studies with longer duration, more numbers of examined genes, higher dose of curcumin, and larger sample size are required.